2011
DOI: 10.1039/c1sm05354j
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependent pathways in spontaneous self-assembly of unilamellar vesicles

Abstract: We report on the structural dynamics underlying the formation of unilamellar vesicles upon mixing dilute solutions of anionic and zwitterionic surfactant solutions. The spontaneous self-assembly was initiated by rapid mixing of the surfactant solutions using a stopped-flow device and the transient intermediate structures were probed by time-resolved small-angle X-ray scattering. The initial surfactant solutions comprised of anionic lithium perfluorooctanoate and zwitterionic tetradecyldimethylamine oxide, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 47 publications
5
77
0
Order By: Relevance
“…Similar unilamellar vesicles can also be formed in the equivalent anionic and cationic surfactant mixtures, but due to the stronger head group interaction the formation process occurs more rapidly [16]. Detailed studies of anioniczwitterionic system have revealed that disk-like transient mixed micelles are involved at higher concentrations above the cmc, while more elongated intermediate structures such as cylinder-like and torus-like mixed micelles are observed at lower concentrations below the cmc of the more soluble component [15]. The transient disk-like micelles formed at higher concentrations are not fully stable and they grow with time by fusion, and beyond a critical size disks close to form unilamellar vesicles [16].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similar unilamellar vesicles can also be formed in the equivalent anionic and cationic surfactant mixtures, but due to the stronger head group interaction the formation process occurs more rapidly [16]. Detailed studies of anioniczwitterionic system have revealed that disk-like transient mixed micelles are involved at higher concentrations above the cmc, while more elongated intermediate structures such as cylinder-like and torus-like mixed micelles are observed at lower concentrations below the cmc of the more soluble component [15]. The transient disk-like micelles formed at higher concentrations are not fully stable and they grow with time by fusion, and beyond a critical size disks close to form unilamellar vesicles [16].…”
Section: Introductionmentioning
confidence: 96%
“…The transient disk-like micelles formed at higher concentrations are not fully stable and they grow with time by fusion, and beyond a critical size disks close to form unilamellar vesicles [16]. At low concentration range, the process is more likely governed by a monomer addition mechanism by which initially formed elongated cylindrical micelles grow until a certain size, beyond that they close to form more globular torus-like shape which then transform to unilamellar vesicles [15]. For concentrations close to the cmc of both surfactants, torus-like mixed micelles are formed spontaneously, which grow predominantly by a monomer addition mechanism in a reservoir of excess soluble surfactant component and eventually transform to unilamellar vesicles.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…11b shows snapshots of TR-SANS data taken during the formation of vesicles on mixing a zwitterionic surfactant, tetradecyl dimethyl amine oxide (TDMAO) and an anionic surfactant, lithium perfluorooctanesulfonate (LiPFOS). 8,138,139 Immediately after mixing, disk-like mixed micelles are formed, evidenced by the region (0.02 o Q o 0.1 Å À1 ) in which I(Q) scales with Q À2 .…”
Section: Time-resolved Sans (Tr-sans)mentioning
confidence: 99%
“…23 The formation process via disc-like micelles has been well established for mixtures of surfactants above the cmc, while new investigations show that the mechanism procedes via a torus-like state, if the anionic surfactant is below the cmc. 24 Generally, in these surfactant mixtures long-time stable unilamellar vesicles are formed spontaneously which do not precipitate. In comparison the corresponding catanionic mixtures with tetradecyltrimethylammonium bromide (TTABr) show a tendency for precipitation after some time.…”
Section: Introductionmentioning
confidence: 99%